A new cryptic species in a new cryptic genus in the Caesalpinia group (Leguminosae) from the seasonally dry inter‐Andean valleys of South America. Issue 3 (25th June 2015) - Gagnon, Edeline; Hughes, Colin E.; Lewis, Gwilym P.; Bruneau, Anne
Abstract: The generic affiliation of the Andean species Caesalpinia trichocarpa, C. mimosifolia, and their close relatives has remained uncertain in all recent studies of Caesalpinia s.l. (Leguminosae, subfamily Caesalpinioideae). A new densely sampled phylogeny based on four DNA sequence regions ( rps16, trn D‐trnT, ycf6‐ psbM, ITS) strongly supports the monophyly of an Andean clade. We propose that despite the lack of obvious diagnostic morphological synapomorphies, this Andean group should be considered as a distinct genus, here described as the new genus Arquita . Phylogenetic analyses also suggest a problem with species delimitation in this group. Within C. trichocarpa, accessions from disjunct geographic areas in Argentina, Bolivia and Peru each form a robustly supported, unresolved clade that includes C. mimosifolia . The morphological and genetic cohesiveness of the C. trichocarpa complex is investigated using morphometric phenetic analyses of qualitative and quantitative flower and leaf traits, and reconstruction of a densely sampled phylogeny using three plastid and one nuclear ribosomal DNA sequence loci. Our results suggest that the most geographically isolated of these clades, narrowly endemic to two inter‐Andean valleys in central‐north Peru and separated by ∼1350 km, and extensive high Andean cordilleras above 4000 m, from the nearest populations in Bolivia, represents a genetically highly distinct and morphologically cryptic lineage here described as a new species ( Arquita grandiflora ). A full taxonomic account of the new genus Arquita and its component species is provided, with a distribution map and a key to the species.